Intercultural Communication Among Togale Women in South Halmahera: Adaptation, Resistance, and Identity Negotiation - Makbul A.H Din; Burhan; Syaifuddin (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
This article reorganizes and strengthens the analysis of intercultural communication among Togale women in South Halmahera. The term Togale refers to a relational social category connecting Tobelo and Galela communities. It does not name a homogeneous ethnic block. The study examines how women negotiate gendered authority through adat, religion, kinship, livelihood, education, and post-conflict memory. The revised argument uses communication ethnography with a critical-postcolonial orientation. It also strengthens the discussion with recent literature on gender norms, women's empowerment, intercultural identity negotiation, indigenous relationality, religious communication, and peacebuilding. Field data came from interviews, participant observation, and documentation conducted in 2025. The analysis follows reflexive thematic analysis and uses Hymes's Speaking model, high-context communication, face negotiation theory, and communication accommodation theory. The findings show that Tobelo and Galela women share relational agency, but they use different symbolic resources. Tobelo women's public authority often grows through education, health work, church-related service, and family mediation. Galela women's public authority often grows through Islamic moral discourse, taklim participation, modesty norms, garden economy, and everyday da'wah. Adat practices such as salay, bobangu, sa'ali, and o dailako protect women's dignity while also regulating speech, mobility, and bodily conduct. The article develops the concept of indigenous gender negotiation to describe culturally grounded agency that works through tradition, religion, and relational ethics rather than outside them. This concept contributes to intercultural communication and multicultural da'wah studies by showing how women sustain moral identity, social coexistence, and practical authority in a post-conflict Muslim-Christian setting.